Organic fertilizer abrasive grits increase soil available nitrogen, plant height, and biomass. Issue 1 (28th August 2020) - Carlson, Michael; Forcella, Frank; Wortman, Sam; Clay, David; Clay, Sharon A.
Abstract: In organic cropping systems, air‐propelled abrasive grits can be used to control in‐row weeds. If the applied abrasive grit is an approved organic fertilizer, these applications may serve a dual purpose of weed control and crop fertility. Laboratory soil incubations examined the N mineralization rates of several grit types with differing C/N ratios (Agra Grit [crushed walnut shells, 170:1], corncob grit [91:1], Sustane [composted turkey litter, 5.0:1], Phytaboost Plant Food [crushed and pelletized soybean meal, 5.0:1]). A greenhouse study determined plant wheat ( Triticum aestivum L.), kale ( Brassica napus pabluaria DC), and velvetleaf ( Abutilon theophrasti Medik.) growth response in soils amended with these grits. The N mineralization rates varied by grit type, soil, and application rate. The N mineralized from Phytaboost within 56 d was similar among the amounts of N a whereas the amount of N mineralized from Sustane was inversely related to the amount of N applied. Agra Grit and corncob grit immobilized soil N due to their high C/N ratios. In soils amended with Sustane, plant height and biomass were 15–43% and 34–83% greater than for plants grown in soils with Agra Grit, corncob grit, and the nontreated soil. Applications of organic fertilizer as air‐propelled grit may improve crop growth; however, if weed control is imperfect, these grits may increase weed growth. Grits with high C/N ratios may immobilize soil available N but not affect plant growth.